Use of indwelling pleural catheters for the definitive treatment of malignant pleural effusion - Abrão,Fernando Conrado (2017)
ABSTRACT Objective: To evaluate the safety and feasibility of the use of indwelling pleural catheters (IPCs) in patients with malignant pleural effusion (MPE). Methods: We prospectively collected data from patients with MPE undergoing IPC placement between January of 2014 and July of 2015. All patients submitted to IPC placement had a life expectancy > 30 days, in accordance with the MPE treatment guidelines established by the British Thoracic Society. The data collected included gender, age, body mass index, primary cancer site, duration of IPC drainage, IPC-related complications, length of hospital stay, pleural effusion recurrence, and occurrence of spontaneous pleurodesis. Results: A total of 19 patients underwent IPC placement during the study period. Median overall survival after IPC insertion was 145 days. The median follow-up among the surviving patients was 125 days (range, 53-485 days), and the median time between catheter insertion and removal was 31 days (range, 2-126 days). There were IPC-related complications in 5 patients (26.2%), and spontaneous pleurodesis was achieved in 8 (42.0%). Among those 8 patients, the IPC was removed between days 30 and 126 in 4, and spontaneous pleurodesis occurred within the first 30 days in 4. Conclusions: The use of IPCs seems to be feasible and safe in patients with MPE.